Growing the fire within: Exploring innovative and successful adult language learning methods in Indigenous communities in Canada and the US - Chew, Kari A. B.; Manatowa-Bailey, Jacob; Lukaniec, Megan; McIvor, Onowa; Linn, Mary (My University, 2021)
This report summarizes the outcomes of a five-day gathering called “Exploring Innovative and Successful Adult Language Learning Methods in Canadian & US Indigenous Communities” at the First Peoples House at the University of Victoria, British Columbia, Feb 18-22, 2020.
Keywords: Language, Linguistics.; Native American Studies.; Education, Bilingual and Multicultural.